Numerical simulation of mechanical heart valve with coherent vortex shedding in OpenFOAM - Zakaria, Mohamad Shukri; Ismail, Farzad; Wiriadidjaja, Surjatin; Aziz, M. F. A.; Tamagawa, Masaaki; Basri, Adi Azriff; Ahmad, Kamarul Arifin (Centre for Advanced Research on Energy, Faculty of Mechanical Engineering, Universiti Teknikal Malaysia Melaka, 2017)
In this paper, coherent structure of the turbulent large eddy simulation (LES) model is visualized through the newly develop high resolution computational fluid dynamics algorithm. The numerical simulation was conducted using Opensource platform, namely OpenFOAM version 2.3.1. A validation is done by comparing with previous experimental data of similar geometry. Results shows, at physiological Re=6000, the LES model produces highly complex turbulent structures contained valuable information that could predict the heart valve disease such as a blood clot.